Modeling firm heterogeneity in corporate social performance and financial performance - Isaksson, L.; Woodside, Arch (Elsevier, 2016)
Prior research on the association between corporate social performance (CSP) and corporate financial performance (CFP) includes conflicting perspectives and inconclusive findings as to whether or not CSP has a positive, negative, or neutral association with CFP. While Wang's (2015) meta-analysis confirms the relationship between CSP and CFP to be significant and positive, in some contexts CSP and CFP associate negatively; CSP may need to receive “good management” support to yield positive financial outcomes (Luo & Bhattacharya, 2009). The study here tests and supports the perspective that “good management” occurs in configurations (i.e., business models) with high CSP to indicate high CFP. A configurational theoretical stance implies that recipes of bad management with high or low CSP are likely to associate with low CFP. Configurational analysis supports this theoretical perspective. Building from complexity theory, a configurational analysis includes the propositions that complex multiple recipes lead to the same outcome (equifinality tenet) whereby variables (ingredients) found to associate causally in one configuration may be absent in another recipe or even inversely related in a third recipe associated with this same outcome. The present study employs a mixed methods research design (using surveys of senior executives, independent CSP firm assessments using ESG factors (environment, social (or human rights), and governance), and analysis of corporate annual reports of 82 mostly highly-global Swedish firms). The study overcomes the mismatch between case-level theory proposals and variable-based data analyses that is widespread in the relevant literature. The study's findings support the core tenets of complexity theory.